New Frontiers in Artificial Intelligence : JSAI-isAI 2014 Workshops, LENLS, JURISIN, and GABA, Kanagawa, Japan, October 27-28, 2014, Revised Selected Papers - Murata, Tsuyoshi; Mineshima, Koji.; Bekki, Daisuke; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the JSAI-isAI 2014 Workshops LENLS, JURISIN, and GABA which tool place on November 2014, in Japan. The 26 contributions in this volume were carefully reviewed and selected from 57 submissions. From the 3 workshops (LENLS11, JURISIN2014, and GABA2014), 23 papers were carefully selected and revised according to the comments of the workshop program committee. LENLS (Logic and Engineering of Natural Language Semantics) is an annual international workshop on formal semantics and pragmatics and it focused on the formal and theoretical aspects of natural language. JURISIN (Juris-informatics) 2014 was the 8th event in the series, the purpose of this workshop was to discuss fundamental and practical issues for juris-informatics, bringing together experts from a variety of relevant backgrounds, including law, social science, information and intelligent technology, logic and philosophy (including the area of AI and law). GABA (Graph-based Algorithms for Big Data and its Applications) 2014 was the first workshop on graph structures including string, tree, bipartite- and di-graph for knowledge discovery in big data. The purpose of this workshop was to discuss ideas for realizing big data integration, including algorithms with theoretical / experimental results.
LENLS 11 -- Logic and Engineering of Natural Language Semantics (LENLS) 11 -- Codability and Robustness in Formal Natural Language Semantics -- CI via DTS -- Formal Analysis of Epistemic Modalities and Conditionals based on Logic of Belief Structures -- A type-logical account of quantification in event semantics -- Towards a Wide-Coverage Tableau Method for Natural Logic -- Resolving Modal Anaphora in Dependent Type Semantics -- Canonical Constituents and Non-canonical Coordination | Simple Categorial Grammar Account -- A good intensifier -- Strict Comparison and Weak Necessity: The Case of Epistemic Yao in Mandarin Chinese -- Computing the Semantics of Plurals and Massive Entities using Many-Sorted Types -- On CG Management of Japanese Weak Necessity Modal Hazu -- Using Signatures in Type Theory to Represent Situations -- Scope as syntactic abstraction -- Focus and Givenness Across the Grammar -- JURISIN 2014 -- Eighth International Workshop on Juris-Informatics (JURISIN 2014) -- Classification of Precedents by Modeling Tool for Action and Epistemic State: DEMO -- Legal Question Answering Using Ranking SVM and Syntactic/Semantic Similarity -- Translating Simple Legal Text to Formal Representations -- Analyzing Reliability Change in Legal Case -- GABA 2014 -- Workshop on Graph-based Algorithms for Big Data and its Applications (GABA2014) -- Anchor Alignment Problem for Rooted Labeled Trees -- Central Point Selection for Dimension Reduction ProjectionSimple-Map using Binary Quantization -- Mapping Kernels for Cyclically Ordered Trees -- Finding Ambiguous Patterns on Grammar Compressed String -- Detecting Anomalous Subgraphs on Attributed Graphs Using Graph Cuts.
Keywords: Artificial intelligence; Information storage and retrieva; Data mining; Computer science; Information systems; Artificial Intelligence; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Mathematical Logic and Formal Languages; Computer Appl. in Administrative Data Processing